맛버섯(Pholiota nameko) 우량균주 선발 및 병 재배법 - 정경주; 최덕수; 최형국; 김정근; 정기철; Jung, Kyung-Ju; Choi, Duck-Soo; Choi, Hyeong-Gug; Kim, Joung-Keon; Chung, Ki-Chul (한국버섯학회지, 2007)
These experiment was conducted to find the superior strain selection, cultivation technique and optimum environmental condition of nameko mushroom culture using plastic container. The results was following as Mycelium of Pholiota nameko grown well at MCM and Hamada media, and its media acidity was pH 6~7. The optimum temperature condition for growing mycelium was $25^{°}C$. Under $15^{°}C$ and above $30^{°}C$ of temperature condition, mycelium growing speed was delayed remarkably. Among the 29 strains of nameko mushroom, the most productive strains was JNM19007, JNM19026, JNM19027 and JNM19028. The optimum media composition rate for produce fruitbody was pine sawdust 80% + wheat bran 20%. In this condition, the average fruitbody amount was 188g per 1,100cc container. The optimum post-culturing period was 50 days and mushroom sprout appeared 7 days after old mycelia removed. The suitable temperature was $12^{°}C$ for induce sprout, growing period was $16^{°}C$ and the optimum relative humidity was 95% in all culturing periods. 맛버섯의 우량균주를 선발하고 병재배에 적합한 환경조건과 재배기술을 찾고자 시험한 결과는 다음과 같다. 맛버섯 균사는 MCM배지와 Hamada배지에서 잘 자랐고, 배지의 적정산도는 pH6~7이었다. 균사생육에 가장 적합한 온도는 $25^{°}C$였으며, $15^{°}C$ 이하와 $30^{°}C$ 이상의 조건에서는 균사생육이 현저하게 늦어졌다. 맛버섯 균주 29계통 중 생산성이 좋은 계통은 JNM19007, JNM19026, JNM19027과 JNM19028이었다. 자실체 생산을 위하여 가장 적합한 배지조성비는 미송톱밥 80%와 밀기울 20%(V/V) 혼합배지로 1,100cc 병당 평균 188g의 자실체가 생산되었다. 최적 후배양기간은 50일 이었으며, 균긁기 후 7일 만에 발이 되었다. 발이유기동안 적정 온도는 $12^{°}C$이었고, 생육기에는 $16^{°}C$였다. 맛버섯 전 재배기간 동안 적합한 상대습도는 95%였다.